Chris Ogden ed. New South Asian Security: Six Core Relations Underpinning Regional Security - Mr. Samran Ali (CISS Insight Journal, 2018)
New South Asian Security: Six Core Relations Underpinning Regional Security is an edited volume on South Asian security by Chris Ogden. Six chapters are written by eminent scholars with an introduction by the editor. They include discussion of different aspects of bilateral relations of the South Asian states. Separate chapters cover the bilateral relations between China-India, Pakistan-Afghanistan, India-Pakistan, China-Afghanistan, China-Pakistan and India-Afghanistan. The book’s introduction explains the its approach to understanding South Asian security problems. Chris Ogden takes a new approach to understand the security dynamics and challenges in South Asia. It pursues the constructivists ideas of identity and norms and eschews comparison with liberal ideas of economic cooperation, multilateralism and to some extent the realist ideas of treating ‘states as identical black boxes’. Instead of discussing specific issues, such as nuclear deterrence, security, terrorism and external perspectives on these issues, the author takes the region as ‘co-dependent entity.’ Relations between the regional powers China, Pakistan, India and Afghanistan are discussed as factors that impact the regional security. These four countries are further placed on the rise and fall spectrum i.e. China and India are dubbed as rising powers and Pakistan and Afghanistan as failing states. It tries to show through a state focused and state driven approaches, that ‘security in South Asia is highly inter-connected and co-dependent in terms of provenance and orientation’ and focuses on interaction among these four states through the interplay of norms under political, physical and security dimensions.